Sexual abuse of children as a form of power abuse and abuse of the body - M. Reynaert (Acta Theologica)
This article investigates the relationship between sexual abuse, power and the body from a Catholic theological viewpoint. The article starts with the relationship between sexual abuse and power. It is argued that sexual abuse is always a form of power abuse. A second step examines the relation between sexual abuse and the body. We may not ignore the theme of the body when we speak about sexual abuse as a form of power abuse. The article also explores whether the body is a theme in recent (theological and popular) literature on sexual abuse. It discusses how the perception of the body has an impact on dealing with the body and potential sexual abuse. The article concludes with a search for an appropriate image of the body that may reduce the prevalence of sexual abuse.